KEUTAMAAN ORANG BERILMU DALAM AL-QUR’AN SURAT AL-MUJADALAH AYAT 11 - Arum Sari, Dewi Fatimah Putri; Retnaningsih, Diah Ayu (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Islam is a religion with the holy Qur'an that highly upholds, positions knowledge and believers. A knowledgeable person will have a positive point of view because of his knowledge and be able to practice it. The purpose of writing this article is to discuss the virtues of knowledgeable people in the Qur'an Surah Al-Mujadalah verse 11 according to several interpretations. That in some interpretations it is ordered to honor others when in the assembly. Further discussion focuses on the manners in the assembly related to the virtues of the knowledgeable person, where in obtaining the virtue of knowledge, a person who demands knowledge must obey the rules of Allah SWT and be civilized when in the assembly. The type of research used in this writing is a type of qualitative research through literature study or library research where all data obtained are primary and secondary sources (from articles, books, journals, other sources) that are in accordance with the title of this article with a descriptive method. Based on the results of the study, it can be concluded that the virtues of knowledgeable people are very noble according to what is contained in Surah Al-Mujadalah verse 11 that Allah SWT promises those who believe and have knowledge will be elevated in degrees, that is the virtue of knowledgeable people.